Chromosome structural analysis : a practical approach - Bickmore, Wendy (Practical approach series, 1999)
The DNA of eukaryotes is packaged into chromosomes - each chromosome consisting of a very long molecule of DNA and various proteins (for example, histones), and the number of chromosomes being characteristic for the species concerned. Chromosome analysis can provide a great deal of information for many aspects of cellular genetics such as DNA replication, The book is structured in a methodical fashion - the introductory chapters are centred around analysis of chromatin with chapters on the mapping of protein: DNA interactions "in vivo" using ligation-mediated PCR and the mapping of chromatin-associated proteins by formaldehyde cross-linking. The next chapters concentrate on the study of whole chromosome structure, including: fission yeast chromosome analysis using FISH and CHIP, isolation of vertebrate metaphase chromosomes and their analysis by FISH, the study of vertebrate chromosome progression through mitosis, and the analysis of mammalian interphase chromosomes by immunofluorescence and FISH. There then follow chapters on FISH in whole-mount tissues and the analysis of the sub-structure of mammalian nuclei "in vitro."